Integrin avB3 acting as membrane receptor for thyroid hormones mediates angiogenesis in malignant T cells - Cayrol, Maria Florencia (2015)
The interaction of lymphoid tumor cells with components of the extracellular matrix via the αvβ3 integrin allows tumor survival and spreading. We have found that thyroid hormones (THs), acting as soluble integrin αvβ3 ligands, activate growth-related signaling pathways in T-cell lymphomas (TCL). Specifically, TH-activated αvβ3 integrin signaling promotes TCL proliferation and angiogenesis, in part, through up-Regulation of VEGF. Consequently, genetic or pharmacologic inhibition of integrin αvβ3 decreases VEGF production and induces TCL cell death in vitro and in human xenografts models. In sum, we show that integrin αVβ3 transduces pro-survival signals into TCL nuclei, suggesting a novel mechanism for the endocrine modulation of TCL pathophysiology. Targeting this mechanism could constitute an effective and potentially low-toxicity chemotherapy-free treatment for TCL patients.